Jejak Pengaruh Kebijakan Politik Pan-Islamisme Sultan Abdul Hamid II (1876-1909 M) di Wilayah Terjajah Umat Muslim Dunia - Bahrudin Lazuardi; Iswan Karim; Muhammad Syamsul Munir (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study provides an in-depth analysis of the impact of Sultan Abdul Hamid II’s (1876–1909 CE) Pan-Islamist policies on the colonized Muslim world and their evolution into the contemporary era. There are four main points in this study, namely: 1) The background to the emergence of Pan-Islamist policies was the urgent domestic and foreign policy conditions facing the Ottoman Empire; 2) Conceptual differences regarding Pan-Islamism between Jamaluddin al-Afghani and Sultan Abdul Hamid II; 3) The process and tactical strategies for spreading the Pan-Islamism movement to the colonized territories; and 4) The traces of influence and the transformation of organizations born from this movement up to the present day. This study employs a comprehensive historical research method, encompassing the stages of data collection (heuristics), source criticism (verification), interpretation, and historiography. The theories applied include the theory of asymmetric political influence to uncover the impact of Ottoman foreign policy, as well as the theory of historical continuity to analyze the bridge connecting past movements to the modern era. The research findings indicate that the Pan-Islamist policy, skillfully championed by Sultan Abdul Hamid II, succeeded in serving as an asymmetric weapon that secured the empire’s sovereignty while simultaneously igniting a massive transnational anti-colonial political consciousness in South Asia, the Dutch East Indies, North Africa, and Central Asia. Furthermore, this study demonstrates that the impact of these movements did not disappear after the collapse of the Ottoman Empire in 1924, but rather underwent a historical transformation that led to the establishment of various major organizations (such as the Khilafat Movement, Sarekat Islam, NU, Muhammadiyah, AUMA, and Jadidism), whose institutional and ideological legacies, as well as the spirit of their global humanitarian diplomacy, still endure and can be felt even in the modern era today.